Pituitary-adrenal-gonadal responses to high-intensity resistance exercise overtraining - Fry, A. C.; Kraemer, W. J.; Ramsey, L. T. (Journal of Applied Physiology, 1998)
Weight-trained men [OT ; n = 11; age = 22.0 ± 0.9 (SE) yr] resistance trained daily at 100% one-repetition maximum (1-RM) intensity for 2 wk, resulting in 1-RM strength decrements and in an overtrained state. A control group (Con; n = 6; age = 23.7 ± 2.4 yr) trained 1 day/wk at a low relative intensity (50% 1 RM). After 2 wk, the OT group exhibited slightly increased exercise-induced testosterone (preexercise = 26.5 ± 1.3 nmol/l, postexercise = 29.1 ± 5.9 nmol/l) and testosterone-to-cortisol ratio (preexercise = 0.049 ± 0.007 nmol/l, postexercise = 0.061 ± 0.006 nmol/l) and decreased exercise-induced cortisol (preexercise = 656.1 ± 98.1 nmol/l, postexercise = 503.1 ± 39.7 nmol/l). Serum concentrations for growth hormone and plasma peptide F [preproenkephalin (107140)] were similar for both groups throughout the overtraining period. This hormonal profile is distinctly different from what has been previously reported for other types of overtraining, indicating that high-relative-intensity resistance exercise overtraining may not be successfully monitered via circulating testosterone and cortisol. Unlike overtraining conditions with endurance athletes, altered resting concentrations of pituitary, adrenal, or gonadal hormones were not evident, and exercise-induced concentrations were only modestly affected.